Exponentially small quantum correction to conductance. (14th October 2022) - Oliveira, Lucas H; Bento, Pedro H S; Novaes, Marcel
Abstract: When time-reversal symmetry is broken, the average conductance through a chaotic cavity, from an entrance lead with N 1 open channels to an exit lead with N 2 open channels, is given by N 1 N 2 / M, where M = N 1 + N 2 . We show that, when tunnel barriers of reflectivity γ are placed on the leads, two correction terms appear in the average conductance, and that one of them is proportional to γ M . Since M ∼ ℏ −1, this correction is exponentially small in the semiclassical limit. We derive this term from a semiclassical approximation, generally expected to give only leading orders in powers of ℏ . Even though the theory is built perturbatively both in γ and in 1/ M, the final result is exact.